A palavração: atos político-performáticos no Coletivoz Sarau de Periferia e Poetry Slam Clube da Luta - Rogerio Meira Coelho (2017)
This dissertation seeks a reflection on contemporary urban poetry saraus in Brazil, prioritizing the research on the Coletivoz Sarau de Periferia held in Belo Horizonte, Minas Gerais, since 2008. I will try to present how the movement affirms itself in the scenario of oral poetry in public and it gains instruments that are characteristic of performance art, of performative acting, among other contemporary movements of the arts of the scene, and how the political-performatic acts of the Word in Action are configured. Investigation and research of the sarau, as well as other movements linked to oral poetry read/recited in public, such as poetry slam, a competition mode of spoken poetry, from primarily the experiences and visits to these meetings spread throughout Brazil and in other countries. As a methodology, interviews and testimonies of active participants were gathered, the survey of the personal experiences and the visitation to the saraus and slams, as well as all historical collection available on the internet and in personal archive of the collectives.The discussion on performance was based on Paul Zumthor's notes on oral poetry, voice and performance, considering Performance, Reception and Reading as his main work (ZUMTHOR, 2007). Public participation in the meetings of saraus and slams and the relationship between protagonists and public-actuator have a structuring role in Nicholas Bourriaud's Aesthetic Relation (2009), when notions of conviviality and the fundamental exchange of roles are fierce. The research, which starts from the contemporary urban saraos in Brazil, at the end, begins a discussion about the poetic performance in poetry slam. It seeks to identify how the "competition" in this modality intensifies the power of the word oralized/recited by means of bodily actions, potentializing the performative power of the poetic word, when there is a relation with an active public, that participates as a "jury", that intuit about the result of the performance and influences the presentation and the movement itself. In Belo Horizonte, the Poetry Slam Clube da Luta, started in 2014, won adepts from the urban saraus, or attracted new sympathizers, renewed by the movement itself. Are the investigated ways of using the body in competition - the imposition of the competitive scene, which provides for the use of the spoken word in poetry slam (without the use of costumes, musical accompaniment, etc.), also reveal a conditioned performance?